Thermal and photostability studies of triprolidine hydrochloride and its mixtures with cyclodextrin and glucose - Ndlebe, Vuyelwa Jacqueline (Rhodes University, Faculty of Science, Department of Chemistry, 2004)
Triprolidine hydrochloride (Câ‚ â‚‰Hâ‚‚â‚‚Nâ‚‚.HCl.Hâ‚‚O) (TPH) is a well-known antihistamine drug. It melts between 118Â°C and 122Â°C and the amount of water present is 4.5 mass percent. TPH is reported as being photosensitive and must be stored in sealed, light-tight containers. The thermal stabilities of TPH and of 1:1 molar and 1:1 mass ratio physical mixtures of TPH with beta-cyclodextrin (BCD) and with glucose have been examined using DSC, TG and TG-FTIR, complemented by X-ray powder diffraction (XRD) and infrared spectroscopic (IR) studies. Thermal studies of the solid TPH/BCD mixtures indicated that interaction between the components occurs and it is possible that the TPH molecule may be least partially accommodated in the cavity of the BCD host molecule. XRD results support this indication of inclusion. The results for mixtures of TPH/glucose also suggest that there is interaction between the two components. The results of molecular modelling suggest that TPH is most likely to be accommodated in the BCD cavity as a neutral triprolidine molecule with the toluene portion of the molecule entering first. There is also an indication that the Z-isomer should be accommodated slightly more readily than the E-isomer. Photostability studies were done by irradiating thin layers of solid samples of TPH and its mixtures for various times at 40Â°C using an Atlas Sun test CPS lamp operating at 550 W h mâ »Â². An analytical method using HPLC was developed and validated to determine the amounts of any photodegradants. DSC, TG, FTIR, XRD and IR were also used examine the irradiated samples. XRD results showed that changes in the TPH crystal structure occurred during irradiation and that these changes increased with the time of irradiation. Irradiation for 20 hours with UV or exposure to sunlight showed the presence of degradants. The results obtained illustrate the general stability of TPH, especially in the solid state. Although the potential for isomerization to the pharmaceutically inactive Z-isomer exists, this transformation would require extreme light conditions. The study has also shown TPH to be compatible with both glucose and BCD, which are potential excipients both in solid and liquid dosage forms. The presents of these excipients in dosage forms will thus not adversely affect the stability and the therapeutic efficacy of TPH. . An analytical method using HPLC was developed and validated to determine the amounts of any photodegradants. DSC, TG, FTIR, XRD and IR were also used examine the irradiated samples. XRD results showed that changes in the TPH crystal structure occurred during irradiation and that these changes increased with the time of irradiation. Irradiation for 20 hours with UV or exposure to sunlight showed the presence of degradants.
Keywords: Antihistamines; Glucose; Cyclodextrins